A study on fresh product supply chain management decisions considering subsidies and different transaction contracts. - Yunting Wu; Aimin Zhu; Lijuan Yu; Wenbo Wang (PLoS ONE)
With the continuous improvement of people's living standards and the increasing demand for high-quality fresh products, enhancing the quality of fresh products has become an urgent and crucial issue that requires attention. Existing studies have shown that strengthening the preservation capacity of fresh products at the origin can effectively improve product quality. Therefore, this paper starts from the perspective of enhancing the freshness preservation level at the origin, considering providing financial subsidies to the supplier from both the government and the retailer's side, introducing the factor of supplier risk aversion behavior, and respectively constructing and solving the Stackelberg game models under wholesale price contract, cost-sharing contract, revenue-sharing contract, and transfer payment contract to explore how government subsidies and risk aversion affect the optimal decisions of members, the freshness of products, and the utility level of the supply chain. The research results indicate that: (1) The increase in government subsidies has a positive impact on the operation of the fresh product supply chain, which will raise wholesale prices, freshness preservation efforts, selling prices, and the overall utility level of the supply chain. (2) The risk aversion of supplier leads to a reduction in transfer payment costs, wholesale prices, and freshness preservation efforts, but this will, in turn, prompt retailer to lower selling prices, thereby enhancing the utility levels of both the retailer and the supply chain entity. (3) The freshness preservation effort by the supplier is higher in transfer payment contracts and cost-sharing contracts with a high cost-sharing ratio. Under transfer payment contracts, supplier and supply chain entity achieve the highest utility levels, while the most efficient utility level of retailer depends on the risk aversion threshold of supplier. When this threshold is exceeded, it will switch to cost-sharing contracts.